Faktor – Faktor yang mempengaruhi Ketepatan Waktu Pelaporan Keuangan (Studi Perusahaan Manufaktur di Bursa Efek Indonesia Tahun Periode 2017-2019) - Ponco Adi Prakoso; Djoko Wahyudi (Universitas Sains dan Teknologi Komputer, 2022)
This study examines the effect of profitability, liquidity, leverage, reputation auditor, firmosize and auditoroopinion on the Timeliness of financial reporting in manufacturing companies listed in BEI period of 2017-2019. Population in this researchais all companies listed on the Indonesia Stock Exchange from 2017 to 2019. Sampel of selection using purposive sampling method and totallyoobtained a 324 sample.